A new nairo-like virus associated with human febrile illness in China. Issue 1 (1st January 2021) - Wang, Yan-Chun; Wei, Zhengkai; Lv, Xiaolong; Han, Shuzheng; Wang, Zedong; Fan, Changfa; Zhang, Xu; Shao, Jianwei; Zhao, Ying-Hua; Sui, Liyan; Chen, Chen; Liao, Ming; et al.
ABSTRACT : Several nairo-like viruses have been discovered in ticks in recent years, but their relevance to public health remains unknown. Here, we found a patient who had a history of tick bite and suffered from a febrile illness was infected with a previously discovered RNA virus, Beiji nairovirus (BJNV), in the nairo-like virus group of the order Bunyavirales . We isolated the virus by cell culture assay. BJNV could induce cytopathic effects in the baby hamster kidney and human hepatocellular carcinoma cells. Negative-stain electron microscopy revealed enveloped and spherical viral particles, morphologically similar to those of nairoviruses. We identified 67 patients as BJNV infection in 2017–2018. The median age of patients was 48 years (interquartile range 41–53 years); the median incubation period was 7 days (interquartile range 3–12 days). Most patients were men (70%), and a few (10%) had underlying diseases. Common symptoms of infected patients included fever (100%), headache (99%), depression (63%), coma (63%), and fatigue (54%), myalgia or arthralgia (45%); two (3%) patients became critically ill and one died. BJNV could cause growth retardation, viremia and histopathological changes in infected suckling mice. BJNV was also detected in sheep, cattle, and multiple tick species. These findings demonstrated that the newly discovered nairo-like virus may be associated with a febrile illness, with the potential vectors of ticks and reservoirs of sheep and cattle, highlighting its public health significance and necessity of further investigation in the tick-endemic areas worldwide.